Etnomatematika di Balik Kerajinan Anyaman Bali - Kadek Rahayu Puspadewi; I Gst. Ngurah Nila Putra (Mathematics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2014)
This paper is study about the existence of ethnomathematics on the Bali woven handicraft. Ethnomathematics is mathematics that grow and develop in a particular culture. Unconsciously, the society use tesselation concepts in making woven handicraft. A tessellation is a special type of pattern that consists of geometric figures that fit without gaps or overlaps to cover the plane. The existence of ethnomathematics on woven handicraft can be used as a source of learning and of course can make learners better understand how their cultural relate with mathematics.